Corpo-cidade: intervenções artísticas com lambe-lambes em espaços urbanos de Santa Maria - RS - Lima, Amanda Pires de Deus (2024)
This master's thesis deals with the creation of urban interventions with a theme linked to the concept of body-city. The motivating purpose of the research lies in developing a process of artistic interventions in the urban space of Santa Maria – RS, based on an idea of body-city, perceiving it as a living and pulsating body through the use of wheatpaste technique. In the body-city, I focus in the spaces in state of atrophy, understood as neighborhoods and villages in privation of the use of the territory - whether in terms of income, education or household-sanitary. For this instance, a space was delimited for poetic investigation and subsequent interference: Vila Maringá, located in Bairro Diácono João Luíz Pozzobon. Walks, photographs, audio recordings, conversations with inhabitants of that space and inscriptions of these experiences on me were components that permeated the research and creation process, which resulted in the series Urban Histology (2023) and 29º42’56”S-53º45’48”O (2023-2024). In Urban Histology (2023), photographs were hybridized, through digital collage in a software, with clippings of images collected from a Photographic Atlas of Human Anatomy, accompanied by poetic writings and later pasted in the same photographed place (Vila Martingá). But in 29º42’56”S-53º45’48”O (2023-2024) the photographs had their cutting-fragments coupled together, forming kind of urban organs and rhizomatic segmentations of resistence, looking for poietic approach of the local in question. The cartography methodology helped in the malleability of the apprehension and procedural construction of the artworks, as well as the theoretical-practical contaminations. The research meets the thought that public spaces are for the collective use, therefore, should be affected and transformed not only by who possesses the great means of construction, but also by the citizens, which carachterizes an exercize of citizenship and autonomy in face of the urban landscape.